(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
A rocking ratchet phenomenon of directed transport is demonstrated. This has been realised with cold rubidium atoms in one dimensional dissipative optical lattice with lin lin configuration. The temperature of the cold atomic cloud is measured by time of flight technique with 29 . The atom number trapped in the MOT is determined using absorption imaging to be atoms. The results show the influence of the atomic current amplitude by varying the lattice beams parameters. One of the lattice beams is modulated with different modulation depths. It shows that highest modulation values have a higher atomic current. The current amplitude is also depending on the modulation frequencies. The results indicate the possibility of existence the vibrational frequency. The harmonic amplitude ratio varied and found the ratchet current is growing with increasing the amplitude of one of the lattice beams and at a certain value goes down